The effect of reflexology on pain perception aspects in nurses with chronic low back pain in Isfahan - Maryam Eghbali Babadi; Fatemeh Nazari; Reza Safari; Samere Abdoli (Wolters Kluwer Medknow Publications, 2016)
Background: The most important part in experiencing and recognizing the threshold of pain is the perception of pain. Reflexology is a kind of complementary therapy which is rooted in the beliefs of the community. This study was aimed to determine the effect of reflexology on pain perception aspects in patients with chronic low back pain. Materials and Methods: This single-blind clinical trial study was performed on 50 nurses with chronic low back pain, who were selected by convenient sampling and then randomly divided into the case and the control groups. Reflexology was conducted for 2 weeks in both groups as three 40-min sessions per week. Perception aspects of pain were measured using the McGill pain perceptual dimension scale score. Data analysis was performed using SPSS. Results: The overall mean scores of perceptual aspects of pain after the intervention in the case and the control groups were 20 ± 5.97 and 29.60 ± 7.38, respectively, and independent t-test showed a statistically significant difference between the two groups (P < 0.001). Comparing the results in the cognitive aspects of pain separately showed a significant difference between the two groups in the aspects of sensory, pain assessment, and diversity before and after the intervention (P < 0.001), but the difference in the emotional aspect was not significant. Conclusions: Reflexology, which can be done by nurses, has the ability to reduce the intensity score and cognitive aspects of pain. Therefore, it is proposed to be included in patients' surveillance.